2022
DOI: 10.3389/fimmu.2022.829210
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells: Angels or Demons in the Pathophysiology of Sepsis?

Abstract: Sepsis is a syndrome characterized by life-threatening organ dysfunction caused by the dysregulated host response to an infection. Sepsis, especially septic shock and multiple organ dysfunction is a medical emergency associated with high morbidity, high mortality, and prolonged after-effects. Over the past 20 years, regulatory T cells (Tregs) have been a key topic of focus in all stages of sepsis research. Tregs play a controversial role in sepsis based on their heterogeneous characteristics, complex organ/tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 185 publications
0
14
0
Order By: Relevance
“…Abnormal CD4+ and CD8+ T cell responses are major components of a dysregulated acquired immune response, and the immune dysfunction of Tregs also contributes to pathogenesis ( 27 ). Improved outcomes in sepsis by increasing the heterogeneous characteristics of Tregs through intervention strategies has been reported ( 28 ). The investigation of associations between immune-related common genes and immune cell fractions in trauma and sepsis patients revealed that the identified immune-related common genes were more or less significantly related to the immune cells concurrently dysregulated in trauma and sepsis, indicating their possible roles in regulating the functions of these immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal CD4+ and CD8+ T cell responses are major components of a dysregulated acquired immune response, and the immune dysfunction of Tregs also contributes to pathogenesis ( 27 ). Improved outcomes in sepsis by increasing the heterogeneous characteristics of Tregs through intervention strategies has been reported ( 28 ). The investigation of associations between immune-related common genes and immune cell fractions in trauma and sepsis patients revealed that the identified immune-related common genes were more or less significantly related to the immune cells concurrently dysregulated in trauma and sepsis, indicating their possible roles in regulating the functions of these immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the immunophenotype CD39 on CD39+ CD8br within the Tregs panel, predicted by genetics, has a negative correlation with the 28-day mortality rate. Tregs constitute a subset of CD4+ lymphocytes known for their negative immune regulatory functions (47). Given their broad regulatory role in the immune system, Tregs hold considerable therapeutic potential for various diseases (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…As with most S. aureus immune responses, the Treg response is complex. Hence, more work is needed to sort out their exact role in patients with low IL-2 ( Gaborit et al., 2020 ; Gao et al., 2022 ). Similarly, IL-17-producing T cells that are associated with hyperactive and pathogenic immune responses are induced in the presence of commensals such as staphylococcal species specifically upon the use of immune checkpoint inhibitors ( Hu et al., 2022 ).…”
Section: Immune Dysfunctions Imposed By S Aureusmentioning
confidence: 99%